Beyond survival: Strengthening community‐based support for parents receiving a family service intervention. Issue 2 (24th October 2022) - Goff, Rachel; Sadowski, Christina; Bagley, Kerryn
Abstract: This paper presents parents' experiences of community support and their recommendations for how their communities, and the services within them, might support their families. Generated through a human‐centred design methodology and using a desire‐centred framework, the findings suggest that parents receiving a family service require support invoking feelings of intimacy, trust, reciprocity, inclusivity, connection and belonging. Parents' recommendations for community support include addressing material and attitudinal constraints impacting on engagement with services; creating non‐judgmental services tailored to their needs but accessed as a last resort; and creating peer‐based opportunities to support each other. Parents reflect that moving beyond basic survival of risk and vulnerability to a position where thriving is possible requires purposeful integration of parent's existing and desired community into service interventions. Facilitating deliberate change at the intersection of community and service support is pertinent to current and future social work policy and practice. Wider opportunities for understanding and enabling the needs and aspirations of parents, which are often overlooked because of a focus on addressing risk and vulnerability, are considered.